Homeopathic Management of Alopecia Based on Causative Factors (Homoeopathy for All, 2024)
Hair is crucial in shaping human  self-image and personal identity.  It's one of the minority of physical  characteristics that can be readily  changed and controlled in accordance  with cultural standards and fashion  fads. Alopecia, often known as  hair loss, is a prevalent issue that  impacts millions of individuals.  Although alopecia areata may occur  at any age, the majority of people  get the disorder early in life. More  than 80% exhibit indications of the  disease before the age of 40, with  40% experiencing symptoms by the  age of 20. According to research,  women are more prone than males to  acquire alopecia areata, and certain  races and ethnicities may be more  susceptible to the disorder. It is  essential to understand the intricate  structure of hair, particularly when  addressing the most prevalent  causes of alopecia. The normal  hair growth cycle can be disrupted  and result in hair loss due to  factors such as stress, hormonal  imbalances, nutritional deficiencies,  and genetic predispositions. Hair  performs fundamental roles like  thermoregulation, friction reduction,  sun protection, and sensory organ  function. Traditionally, hair on the  head was considered a defensive  shield and is still considered a prime  symbol of personal identity. Yet,  a range of hair-related problems  including alopecia, insufficient hair  growth, early graying, dandruff,  thinning, and lack of shine are  typical worries. The variety of  features of hair, including its form,  length, diameter, texture, and colour,  along with the structure of its cross section, might impact the curl of the  hair.
Keywords: Alopecia; cultural standards; homeopathy